Compressibility of orthorhombic perovskites. The effect of transition metal ions (TMI). (December 2015) - Ardit, Matteo
Abstract: Interest in perovskites evenly spans Materials Science and Geophysics. Due to their inimitably lattice flexibility enabling small as well as large ions to be accommodated, perovskites have become a base structure for new technological applications. Understanding the mechanisms governing their evolution at non-ambient conditions (such as high-pressure and high-temperature) is fundamentally important both for devising functional materials and in order to provide the most reliable possible deep-Earth model. With particular attention being paid to the chemical nature of the constituent ions, a suite of orthorhombic perovskites has been selected and contrasted using several parameterizations and models. A new perspective on the pressure-induced distortion of orthorhombic perovskite structures has enabled their compressional behaviour to be redefined. Graphical abstract: Highlights: Overview of the high-pressure evolution of AB O3 orthorhombic perovskites. Review of several models to systematise the behaviour of these compounds at HP. Constant evidence of a dichotomy between A 2+ B 4+ O3 and A 3+ B 3+ O3 perovskites. Systematic dualism in A 3+ B 3+ O3 if transition metal ions are hosted at B site. New perspective on the pressure-induced distortion of orthorhombic perovskites.